Dispersion management in organic liquid-cladding photonic crystal fiber based on GeSe\(_2\)–As\(_2\)Se\(_3\)–PbSe chalcogenide - Le, Van Hieu (Communications in Physics, 2025)
We present a numerical study of the influence of the liquids on fiber properties. The PCF was proposed based on the GeSe2–As2Se3–PbSe chalcogenide, infiltrated with six organic liquids in air holes in the cladding. The guiding properties in terms of dispersion characteristics, mode area, nonlinear coefficient, and confinement loss of the fundamental mode were numerically investigated. The result is that it is possible to shift the wavelength of the zero dispersion by about 20 nm to longer wavelengths and to reduce the slope of the dispersion curve of the fiber by the liquid filling. The results obtained also show that the PCF has a larger mode area (lower nonlinear coefficient) when infiltrated with liquids with a higher refractive index. At the same time, the presence of liquid in the cladding is responsible for the increase in confinement loss. In particular, the fiber has a lower confinement loss when infiltrated with liquids with a higher refractive index.